Prevalence and correlative-statistical interrelation of the dysfunction of the intestinal mucosal barrier in children with symptoms of the food hypersensitivity - Olga Pakholchuk (ScienceRise: Medical Science, 2018)
Food intolerance (FI) in children is one of the most common manifestations of allergy in early childhood, which is confirmed by the results of many epidemiological studies. Studies have shown that the degree of permeability of the intestinal wall is an important link not only in the pathogenesis of FI, but also in the formation of processes of immune tolerance and maturation of immunity.